Loss of zinc‐finger protein 143 contributes to tumour progression by interleukin‐8‐CXCR axis in colon cancer. Issue 6 (1st April 2019) - Verma, Vikas; Paek, A Rome; Choi, Beom-Kyu; Hong, Eun Kyung; You, Hye Jin
Abstract: Several studies have shown that expression of zinc‐finger protein 143 (ZNF143) is closely related to tumour progression including colon cancer. However, it remains unclear how ZNF143 expression is related to tumour progression within the tumour microenvironment. Here, we investigated whether ZNF143 expression affects the tumour microenvironment and tumour progression by screening molecules secreted by colon cancer cells stably expressing short‐hairpin RNAs against ZNF143 or control RNAs. We observed that secretion of interleukin (IL)‐8 was increased when ZNF143 expression was reduced in two colon cancer cell lines. The mRNA and protein levels of IL‐8 were increased in cells following ZNF143 knockdown, and this effect was reversed when ZNF143 expression was restored. The Janus tyrosine kinase/signal transducer and activator of transcription (JAK/STAT) and extracellular signal‐regulated kinase pathways were also shown to contribute to IL‐8 expression in ZNF143‐knockdown cells. The expression levels of ZNF143 and IL‐8 were inversely correlated with three‐dimensionally grown spheroids and colon cancer tissues. THP‐1 cells were differentiated when cells were incubated with condition media from colon cancer cell with less ZNF143, drastically. Loss of ZNF143 may contribute to the development of colon cancer by regulating intracellular and intercellular signalling for cell plasticity and the tumour microenvironment respectively.